Pengaruh Keputusan Investasi, Keputusan Pendanaan, dan Pertumbuhan Perusahaan terhadap Nilai Perusahaan - Rayhan Dwi Tirtanata; Ayumi Rahma (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to examine and obtain empirical evidence regarding the effect of Investment Decisions, Funding Decisions, and Company Growth on Firm Value in banking sub-sector companies listed on the Indonesia Stock Exchange during the period 2019 to 2023. This study uses a descriptive quantitative approach with purposive sampling method in sample selection, resulting in 205 observations. The data were analyzed using panel data regression techniques with the help of Eviews 12 software. The results showed that simultaneously, Investment Decisions, Funding Decisions, and Company Growth had an effect on Firm Value. But partially, Company Growth has a positive influence on Firm Value. Meanwhile, Investment Decisions and Funding Decisions have no effect on Firm Value. This finding indicates that the company growth factor is more considered by investors in assessing the value of banking companies, compared to other managerial decisions. Based on these results, it is recommended for companies to focus more on sustainable growth strategies to increase company value in the eyes of investors and other stakeholders.